Dissemination of the multidrug-resistant extended-spectrum β-lactamase-producing Escherichia coli O25b-ST131 clone and the role of house crow (Corvus splendens) foraging on hospital waste in Bangladesh. (November 2015) - Hasan, B.; Olsen, B.; Alam, A.; Akter, L.; Melhus, Å.
Abstract: Two hundred and thirty-eight faecal samples from crows foraging on hospital wastes were analysed for extended-spectrum β-lactamase (ESBL)-producing Enterobacteriaceae . ESBL-producing crow isolates were characterized and compared with 31 patient isolates. Among the crows, 59% carried ESBL producers. These included Escherichia coli, Klebsiella pneumoniae, Raoultella terrigena and Enterobacter cloacae harbouring the genes for CTX-M-1, CTX-M-15, CTX-M-55, CTX-M-79, and CTX-M-14. Human isolates carried only the CTX-M-15 gene. Two-thirds of crow E. coli isolates and all human E. coli isolates were multidrug resistant. Crows and patients shared E. coli sequence types, including the epidemic E. coli O25b-ST131 clone. The scavenging behaviour of crows at poorly managed hospital waste dumps made them potential reservoirs of antibiotic resistance, including ESBLs.